Model and Effectiveness of Endurance Exercise to Increase Physical Fitness in Intellectual Disability Subjects with Obesity: A Randomized Controlled Trial - Tirza Z Tamin; F.H. Idris; M. Mansyur; Sidartawan Soegondo (Acta Medica Indonesiana)
Aim: to design a model and assess the effectiveness of endurance exercise to increase physical fitness in intelectual disability (ID) patients with obesity. Methods: a randomized-controlled clinical trial was performed in ID patients with obesity aged 10-30 years old from all Special School in DKI Jakarta, which were randomly allocated into 3 groups and then given 3 different type of exercises: lower extremity muscles endurance exercise for 20 RM followed by cardiorespiratory endurance exercise for 24-25 minutes (type I), lower extremity muscles endurance exercises for 10 RM followed by cardiorespiratory endurance exercises for 26-27 minutes (type II), and threw a tennis ball with 10 m distance for 10 minutes as control (type III). These program was performed 3 times a week for 4 months. Assesment of the exercise effectiveness was done by measuring maximum load that can be lifted and six-minutes walking test on rectangular track which was converted with the VO2 max prediction formula. Analysis was perfomed with Kruskal Wallis test. Results: two hundred and twelve (212) subjects were included in the study, randomly allocated into three types (I, II, and III) of exercises groups. The type II of endurance exercise model was proved to be more effective in increasing lower extremity muscles endurance level compared to type I and III for ID patients with obesity (p<0.05). Meanwhile, type I of endurance exercise model was proved to be more effective in increasing cardiorespiratory endurance level compared to type II and III for ID patients with obesity (p<0.05). Conclusion: lower extremity muscles endurance exercise followed by a cardiorespiratory endurance exercise can be used to increase physical fitness in ID patients with obesity.